Supporting CORBA Applications in a Mobile Environment - Haahr, Mads; Cahill, Vinny; Cunningham, Raymond (My University, 1999)
CORBA, the Common Object Request Broker Architecture, defines a framework for developing object-oriented distributed applications. Unfortunately, current implementations of CORBA have not been designed with support for mobile computers in mind. Using CORBA in a mobile environment raises a number of problems due to hardware mobility and the characteristics of wireless networks. This paper identifies and discusses these problems and presents the design and implementation of our Architecture for Location Independent CORBA Environments (ALICE). ALICE allows CORBA objects running on mobile devices to interact transparently with objects hosted by off-the-shelf CORBA implementations. Importantly, ALICE allows server as well as client objects to reside on mobile hosts without relying on a centralised location register to keep track of their whereabouts.
5th IEEE International Conference on Mobile Computing and Networking (MobiCom '99)
Keywords: Mobile devices; Object-oriented distributed applications